Determining the reliability of a custom built seated stadiometry set-up for measuring spinal height in participants with chronic low back pain. (March 2016) - Steele, James; Bruce-Low, Stewart; Smith, Dave; Jessop, David; Osborne, Neil
Abstract: Indirect measurement of disc hydration can be obtained through measures of spinal height using stadiometry. However, specialised stadiometers for this are often custom-built and expensive. Generic wall-mounted stadiometers alternatively are common in clinics and laboratories. This study examined the reliability of a custom set-up utilising a wall-mounted stadiometer for measurement of spinal height using custom built wall mounted postural rods. Twelve participants with non-specific chronic low back pain (CLBP; females n = 5, males n = 7) underwent measurement of spinal height on three separate consecutive days at the same time of day where 10 measurements were taken at 20 s intervals. Comparisons were made using repeated measures analysis of variance for 'trial' and 'gender'. There were no significant effects by trial or interaction effects of trial x gender. Intra-individual absolute standard error of measurement (SEM) was calculated for spinal height using the first of the 10 measures, the average of 10 measures, the total shrinkage, and the rate of shrinkage across the 10 measures examined as the slope of the curve when a linear regression was fitted. SEMs were 3.1 mm, 2.8 mm, 2.6 mm and 0.212, respectively. Absence of significant differences between trials and the reported SEMs suggests this custom set-up for measuring spinal height changes is suitable use as an outcome measure in either research or clinical practice in participants with CLBP. Highlights: Stadiometers can yield useful information regarding the spine. Most specialised stadiometers for this purpose are custom built and expensive. This study examined the reliability of a set-up using a wall mounted stadiometer. This inexpensive set-up was found to be reliable and thus suitable.